Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Akidah Akhlak Melalui Metode Lectures Vary - Fatimatuzahroh, Fitri; Nurteti, Lilis; Koswara, S. (Jurnal Penelitian Pendidikan Islam, 2019)
This study aims to discuss learning planning, learning implementation, and student learning outcomes of Akidah Akhlak subject, specifically material about "avoiding despicable morals" using the “lectures vary” method in class V MI Kiarapayung Ciamis. The method used is the Kurt Lewin model of classroom action research (CAR). While the data collection techniques used were observation, tests, interviews, documentation and data were analyzed descriptively. After conducting research in class V MI Kiarapayung, Rancah Subdistrict, Ciamis District, the learning outcomes of students using the “lectary vary” learning method have increased, namely an average pre-cycle of 72.8 with completeness of 44%, cycle I an average of 81.6 with completeness 72%, cycle II averaged 96 with completeness 96%, and cycle III averaged 96.8 with 100% completeness. Thus, the “lectures vary” learning method can improve student learning outcomes.